Strengthening Bolivian Competitiveness : Export Diversification and Inclusive Growth - World Bank (World Bank, 2012)
Bolivia's trade liberalization, launched in the mid-1980s, has resulted in a relatively open trade regime; but the results have been mixed. Bolivia's export to Gross Domestic Product (GDP) ratio and export entrepreneurship index rating are among the highest in the Latin American and Caribbean (LAC) region and the country has achieved great success in making soya the major export crop in less than 10 years. At the same time, the country's share in world trade has stagnated and exports are increasingly dominated by gas and minerals. Reinvigorating the nontraditional export sector is important for the government of Bolivia as it implements its national development plan. As a resource-rich country, the Bolivian government's emphasis on export diversification is well-placed but the optimal nontraditional export strategy should build on successes in the traditional sector. This study investigates: (a) the role trade should play in Bolivia's development strategy considering the country's natural resource endowment; (b) the lessons of Bolivia's integration to the world economy; (c) the linkages between Bolivia's past trade and economy and a forward-looking analysis of the impact of different scenarios on growth, employment, trade flows, and poverty; (d) constraints to higher export competitiveness and weaknesses related to transport and logistics; and (e) the characteristics of exporting firms and the constraints affecting them. The main findings of the analysis are that preferential access to world markets is necessary but not sufficient for success in nontraditional exports; rather, success depends largely on increasing the competitiveness of exporting firms. Second, a neutral incentive regime is essential to the growth of nontraditional exports. Third, efficient backbone services are vital for reducing exporters' costs. Finally, the government should be proactive in addressing institutional impediments to cross-border trade. The study presents prioritized policy implications of the analysis related to: (i) trade policy and preferential access to markets; (ii) the incentives regime; (iii) backbone services; (iv) increasing the effectiveness of institutions to promote cross-border trade; and (v) setting the foundations for exports diversification.